Transition‐Metal‐Free Magnesium‐Based Batteries Activated by Anionic Insertion into Fluorinated Graphene Nanosheets. (30th September 2015) - Xie, Junjie; Li, Chilin; Cui, Zhonghui; Guo, Xiangxin
Abstract : Considering resource abundance, high volumetric energy density, and safer anodic electroplating, the Mg‐based battery is thought to be one of the most promising systems beyond current Li‐ion batteries. However, the development of Mg batteries is hindered by the narrow electrochemical window of electrolytes as well as by inapplicable cathode frameworks. In this work, it is proposed, for the first time, to utilize a fast surface redox process to replace sluggish lattice migration for improving the kinetics of Mg batteries. Taking fluorinated graphene nanosheets (FGSs) as model material, a reversible capacity higher than 100 mAh g −1 is achieved in a pseudocapacitance behavior from 2.75 to 0.5 V. Different from traditional storage mechanisms, this proof‐of‐concept Mg/FGS system is activated by a prior anionic process followed by reversible cationic storage. The dilution of charge density by forming large‐sized monovalent complex cations and the easy access to surface redox sites are responsible for the negligible voltage polarization without an evident MgF2 nucleation phenomenon. Abstract : A fast surface redox process is proposed to replace sluggish lattice migration for improving the performance of Mg based batteries. The proof‐of‐concept Mg/fluorinated graphene nanosheet system is activated by a prior anionic process followed by reversible cationic storage with a capacity higher than 100 mAh g −1 in a pseudocapacitance behavior from 2.75 to 0.5 V.